Antibiotic impregnated catheters and intrathecal antibiotics for CSF shunt infection prevention in children undergoing low-risk CSF shunt surgery - Podkovik, Stacey; Zhou, Chuan; Coffin, Susan E.; Hall, Matthew; Hauptman, Jason S.; Kronman, Matthew P.; Mangano, Francesco T.; Pollack, Ian F.; Sedano, Sabrina; Vega, Joaquin; Schaffzin, Joshua K.; Thorell, Emily; et al. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Cerebrospinal fluid (CSF) shunts allow children with hydrocephalus to survive and avoid brain injury (J Neurosurg 107:345-57, 2007; Childs Nerv Syst 12:192-9, 1996). The Hydrocephalus Clinical Research Network implemented non-randomized quality improvement protocols that were shown to decrease infection rates compared to pre-operative prophylactic intravenous antibiotics alone (standard care): initially with intrathecal (IT) antibiotics between 2007–2009 (J Neurosurg Pediatr 8:22-9, 2011), followed by antibiotic impregnated catheters (AIC) in 2012–2013 (J Neurosurg Pediatr 17:391-6, 2016). No large scale studies have compared infection prevention between the techniques in children. Our objectives were to compare the risk of infection following the use of IT antibiotics, AIC, and standard care during low-risk CSF shunt surgery (i.e., initial CSF shunt placement and revisions) in children. Methods A retrospective observational cohort study at 6 tertiary care children’s hospitals was conducted using Pediatric Health Information System + (PHIS +) data augmented with manual chart review. The study population included children ≤ 18 years who underwent initial shunt placement between 01/2007 and 12/2012. Infection and subsequent CSF shunt surgery data were collected through 12/2015. Propensity score adjustment for regression analysis was developed based on site, procedure type, and year; surgeon was treated as a random effect. Results A total of 1723 children underwent initial shunt placement between 2007–2012, with 1371 subsequent shunt revisions and 138 shunt infections. Propensity adjusted regression demonstrated no statistically significant difference in odds of shunt infection between IT antibiotics (OR 1.22, 95% CI 0.82–1.81, p = 0.3) and AICs (OR 0.91, 95% CI 0.56–1.49, p = 0.7) compared to standard care. Conclusion In a large, observational multicenter cohort, IT antibiotics and AICs do not confer a statistically significant risk reduction compared to standard care for pediatric patients undergoing low-risk (i.e., initial or revision) shunt surgeries.